Private Delhi - Patterson, James, 1947-.; Sanghi, Ashwin; Deu, Amerjit, 1960-; Ghatak, Raj (New York, NY Hachette Audio, 2016)
When Santosh Wagh isnt struggling out of a bottle of whisky hes head of Private India, the Mumbai branch of the worlds finest PI agency. In a city of over thirteen million he has his work cut out at the best of times. But now someone is killing women--seemingly unconnected women murdered in a chilling ritual, with strange objects placed carefully at their death scenes. As Santosh and his team race to find the killer, an even greater danger faces Private India--a danger that could threaten the lives of thousands of innocent Mumbai citizens.
Keywords: Private investigators -- India; Mumbai; Fiction; Delhi (India) -- Fiction; Thrillers (Fiction); Suspense fiction